2018
DOI: 10.1177/0883073818798194
|View full text |Cite
|
Sign up to set email alerts
|

Superior Performance in Prone in Infants With Congenital Heart Disease Predicts an Earlier Onset of Walking

Abstract: Infants with congenital heart disease are at risk of impaired neurodevelopment, which frequently manifests as motor delay during their first years of life. This delay is multifactorial in origin and environmental factors, such as a limited experience in prone, may play a role. In this study, we evaluated the motor development of a prospective cohort of 71 infants (37 males) with congenital heart disease at 4 months of age using the Alberta Infant Motor Scales (AIMS). We used regression analyses to determine wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…35 Finally, a recent study of our interdisciplinary team revealed that the ability to maintain the prone prop position in 4-months old infants with CHD resulted in an earlier onset of walking. 28 Altogether, these findings bring additional support to the idea that early motor experience may influence later motor development in high-risk populations and represents a modifiable factor that should be considered by health care professionals to optimize neurodevelopmental outcome.…”
Section: Effect Of Early Individualised Motor Interventionsupporting
confidence: 54%
See 1 more Smart Citation
“…35 Finally, a recent study of our interdisciplinary team revealed that the ability to maintain the prone prop position in 4-months old infants with CHD resulted in an earlier onset of walking. 28 Altogether, these findings bring additional support to the idea that early motor experience may influence later motor development in high-risk populations and represents a modifiable factor that should be considered by health care professionals to optimize neurodevelopmental outcome.…”
Section: Effect Of Early Individualised Motor Interventionsupporting
confidence: 54%
“…These perturbations likely arise from a complex interplay between prenatal, surgical and environmental risk factors that lead to brain injury and dysfunction. 7,21,22 In fact, brain injury acquired during the foetal, the postnatal or the perioperative periods, [23][24][25][26][27] combined with a lack of motor experience, 28 were shown to contribute to these impairments.…”
Section: Motor Functions and Interventionsmentioning
confidence: 99%
“…We found no significant differences between groups for gross motor functions. Since gross motor impairments are known to be the first manifestations of altered neurodevelopment in infants with CHD, it is possible that family physicians and pediatricians, even outside specialized clinics, may be successful at detecting these difficulties and thus accurately referred patients to relevant rehabilitation services or offer parental recommendations on how to foster the child's motor development ( 67 ). Based on parental reports, 18% of children in the Historical Control Group had received treatments with a physical therapist in addition to the standard health care, physical therapy being one of the most frequently received interventional services.…”
Section: Discussionmentioning
confidence: 99%
“…10,11,81,82 In addition, factors that are known to be associated with motor developmental delays in children after early cardiac surgery are long-term DHCA, older age at surgery, a higher number of and longer hospital stays, immobilization after one or more open heart surgical procedures, a higher number of days in the intensive care unit, palliative procedures, lower pre-and postoperative neurological scores, presence of microcephaly, history of epileptic seizures, and oxygen saturation levels below 85%. 39,48,50,51,55,[83][84][85][86][87] Although the worst motor developmental scores were seen in children with SVP, studies including children with other CCHD diagnostic groups show relatively low motor scores as well. The study of Sun et al 71 showed smaller brain volumes in children with SVP, TGA, TOF, and IAA compared with other CHD subgroups and healthy controls.…”
Section: Cardiac Diagnosis and Other Factors Related To Motor Outcomementioning
confidence: 99%